Incidence and determinants of mortality and morbidity following early antiretroviral therapy initiation in HIV-infected adults in West Africa. - (:unkn) unknown (My University, 2007)
OBJECTIVE: To estimate the incidence and risk factors of mortality and severe morbidity during the first months following antiretroviral therapy (ART) initiation in West African adults. METHODS: A cohort study in Abidjan in which 792 adults started ART with a median CD4 cell count of 252 cells/mul and were followed for a median of 8 months. Severe morbidity was defined as all World Health Organization stage 3 or 4-defining morbidity events other than oral candidiasis. RESULTS: In patients with pre-ART CD4 cell count < 200, at 200-350 and > 350 cells/mul, incidence of mortality was 5.0 [95% confidence interval (CI), 2.6-8.7], 1.7 (95% CI, 0.6-3.8) and 0.0 (95% CI, 0.0-3.4]/100 person-years, and incidence of severe morbidity was 13.3 (95% CI, 9.0-19.1), 9.5 (95% CI, 6.2-12.9) and 7.9 (95% CI, 3.4-15.5)/100 person-years, respectively. The most frequent diseases were invasive bacterial diseases (32/65 episodes, 49%) and tuberculosis (25/65 episodes, 38%). Both diseases followed the same curve of decreasing incidence over time. Patients who experienced severe morbidity had higher risks of mortality, virological failure and immunological failure. Other independent risk factors for mortality and/or severe morbidity were: at baseline, high viral load, advanced clinical stage, past history of tuberculosis, low BMI, low haemoglobin and low CD4 cell count; during follow-up: low CD4 cell count and persistently detectable viral load. CONCLUSION: These data give new arguments to reinforce the hypothesis that, in this region, ART should be started before the CD4 cell count drops below 350 cells/mul. Further studies should assess whether patients with low BMI, low haemoglobin, high viral load or past history of tuberculosis should start ART earlier.
Keywords: African Research